CURING CHARACTERISTIC OF VARIOUS ACCELERATORS ON NATURAL RUBBER/CHLOROPRENE RUBBER BLENDS - Noor Maryam Setyadewi; Hesty Eka Mayasari (Jurnal Dinamika Penelitian Industri, 2020)
The effects of the various accelerator of natural rubber (NR) and chloroprene (CR) blends on the cure characteristics was investigated in this paper. Blending process of  elastomers NR and CR were prepared by using laboratory two-roll mill. Several types of an accelerator, namely diphenyl guanidine (DPG), 2-mercaptobenzothiazol (MBT), N-tert-butyl-2-benzothiazyl sulphenamide (TBBS), ethylene thiourea (ETU), and tetramethyl thiuram monosulfide (TMTM) was used to find out curing characteristics of compound NR/CR (coded A, B, C, D, E). Rheology was studied with a rheometer. Research results show that type of used accelerator and vulcanization temperature influenced scorch time (ts2), optimum vulcanization time (tc90) and cure rate index (CRI) of NR/CR rubber blends. Keywords: accelerator, chloroprene rubber, curing characteristic, natural rubber, scorch time